2020
DOI: 10.1007/s00227-020-03755-1
|View full text |Cite
|
Sign up to set email alerts
|

Trophodynamics at the Longqi hydrothermal vent field and comparison with the East Scotia and Central Indian Ridges

Abstract: The Longqi vent field, situated on the Southwest Indian Ridge, is ecologically distinct among known hydrothermal vents fields. It hosts a combination of previously unknown species and those shared at species or genus level with other hydrothermal vents on the Central Indian Ridge (CIR) and East Scotia Ridge (ESR). We investigate the size-based and trophodynamics of consumers at Longqi vent field and compared these with ESR and CIR vent fields using stable isotope analysis. Intra-specific variability in δ13C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Few studies have investigated food web structures of macrofaunal communities in the Indian vents and reported that these communities possessed 2-4 trophic levels (Van Dover et al, 2001;Copley et al, 2016;Reid et al, 2020). These short trophic chains are typical of other vent communities [e.g., in the EPR (Gaudron et al, 2012;Reid et al, 2013), Juan de Fuca Ridge (Bergquist et al, 2007;Sweetman et al, 2013;Lelièvre et al, 2017), and MAR (Vereshchaka et al, 2000)].…”
Section: Food Websmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have investigated food web structures of macrofaunal communities in the Indian vents and reported that these communities possessed 2-4 trophic levels (Van Dover et al, 2001;Copley et al, 2016;Reid et al, 2020). These short trophic chains are typical of other vent communities [e.g., in the EPR (Gaudron et al, 2012;Reid et al, 2013), Juan de Fuca Ridge (Bergquist et al, 2007;Sweetman et al, 2013;Lelièvre et al, 2017), and MAR (Vereshchaka et al, 2000)].…”
Section: Food Websmentioning
confidence: 99%
“…The dominant macrofaunal species are typically symbiotic primary consumers. Unique stable isotope signatures and additional evidence from in situ hybridization and hologenomic analyses revealed that these dominant taxa rely heavily or exclusively on chemosymbionts for food, including C. squamiferum ( Van Dover, 2002;Goffredi et al, 2004;Nakagawa et al, 2014;Chen et al, 2015b;Reid et al, 2020), Gigantopelta aegis (Copley et al, 2016;Lan et al, 2021), Alviniconcha marissindica (Miyazaki et al, 2020;, R. kairei (Zbinden et al, 2008;Petersen et al, 2010;Guri et al, 2012;Jiang et al, 2020), and B. marisindicus (Yamanaka et al, 2003;McKiness and Cavanaugh, 2005;Copley et al, 2016). With the exception of C. squamiferum and G. aegis, symbiosis was known for congeneric species of these taxa in other oceans (Belkin et al, 1986;Stein et al, 1988;Endow and Ohta, 1989;Nelson et al, 1995;Rieley et al, 1999;Won et al, 2003).…”
Section: Food Websmentioning
confidence: 99%
See 1 more Smart Citation
“…Geological or hydrodynamic barriers thus could be a more important determinant of connectivity between these vent communities than ridge characteristics such as spreading rate. The Longqi and Duanqiao populations share community components with the CIR, the MAR, and the East Scotia Ridge, and have been suggested to be a separate province (Zhou et al, 2018;Reid et al, 2020;Zhou et al, 2022). The northern SWIR vent Tiancheng would be part of the CIR-nSWIR province (Zhou et al, 2022).…”
Section: Vent Fields Of the South-west Indian Ridgementioning
confidence: 99%
“…However, some Indian-endemic species are thought to have low dispersal abilities due to negatively buoyant larvae or eggs, including the peltospirid snails Chrysomallon squamiferum, Gigantopelta aegis, Dracogyra subfuscus, and Lirapex politus (CR) (Chen et al, 2014), or the crab Kiwa sp. "SWIR" (Reid et al, 2020). Habitat degradation and fragmentation due to anthropogenic disturbance may lead to local loss of biodiversity (Pardini et al, 2017;van Dover et al, 2017;Niner et al, 2018) and ecosystem services (Le et al, 2017).…”
Section: Longqi (37°47's 49°39'e 2755m)mentioning
confidence: 99%